2001
DOI: 10.1007/s007750100248
|View full text |Cite
|
Sign up to set email alerts
|

Titanium(IV) targets phosphoesters on nucleotides: implications for the mechanism of action of the anticancer drug titanocene dichloride

Abstract: Reactions between the anticancer drug titanocene dichloride (Cp2TiCl2) and various nucleotides and their constituents in aqueous solution or N,N-dimethylformamide (DMF) have been investigated by 1H and 31P NMR spectroscopy and in the solid state by IR spectroscopy. In aqueous solution over the pH* (pH meter reading in D2O) range 2.3-6.5, CMP forms one new species with Ti(IV) bound only to the phosphate group. In acidic media at pH*<4.6, three species containing titanocene bound to the phosphate group of dGMP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 36 publications
1
64
0
Order By: Relevance
“…To elucidate the specificity of titanium dichloride to DNA, several spectroscopic studies have also been performed using various nucleotides. The interaction between Cp 2 TiCl 2 and 5 -GMP, 5 -AMP, 5 -CMP and 5 -TMP have been investigated in aqueous solution and have shown that both phosphate (O) and nucleobase (N) are possible binding sites in the interaction Ti-DNA [26]. This raises the important issue as to how these compounds mediate their down stream cellular effects, which is currently under investigation.…”
Section: Discussionmentioning
confidence: 98%
“…To elucidate the specificity of titanium dichloride to DNA, several spectroscopic studies have also been performed using various nucleotides. The interaction between Cp 2 TiCl 2 and 5 -GMP, 5 -AMP, 5 -CMP and 5 -TMP have been investigated in aqueous solution and have shown that both phosphate (O) and nucleobase (N) are possible binding sites in the interaction Ti-DNA [26]. This raises the important issue as to how these compounds mediate their down stream cellular effects, which is currently under investigation.…”
Section: Discussionmentioning
confidence: 98%
“…Most interestingly, the binding to the DNA occurred rather via the phosphate backbone than via the nucleobases [85,88]. Binding studies suggested that the cellular uptake of titanocene dichloride may be mediated by the iron transport protein transferrin [89].…”
Section: Titanium Compoundsmentioning
confidence: 99%
“…Therefore, these systems are promising candidates for delivery of treatments using the enhanced permeability and retention (EPR) effect. O,O-ligands have been used to prevent arene-Ru complexes from hydrolysing in RAPTA analogs derivatised with a sugar-bearing phosphate ligand and a biscarboxylate as chelator (77). 170 The Ru-P bond appears to stabilise the O,Ocomplex by accepting electron density.…”
Section: Figure 27mentioning
confidence: 99%